2021
DOI: 10.1016/j.isci.2021.102155
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of text mining in materials research

Abstract: Research publications are the major repository of scientific knowledge. However, their unstructured and highly heterogenous format creates a significant obstacle to large-scale analysis of the information contained within. Recent progress in natural language processing (NLP) has provided a variety of tools for high-quality information extraction from unstructured text. These tools are primarily trained on non-technical text and struggle to produce accurate results when applied to scientific text, involving spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 109 publications
(146 reference statements)
0
104
0
Order By: Relevance
“…To overcome this shortcoming, NLP efforts have been developed and applied to collect and curate synthesis data in relevant literature, such as synthesis conditions and resulting phases 25,98,99,160 . However, because of inherent biases in published results, the lack of negative examples (i.e., failed synthesis attempts) limits the ability to learn which factors contribute to an experiment's success 100,161 . Interestingly, the potential of coupling NLP with autonomous synthesis platforms has been demonstrated by the work of Mehr et al, where a fully integrated system was built to carry out the synthesis of organic compounds with experimental parameters parsed directly from the literature 162 .…”
Section: Decision Makingmentioning
confidence: 99%
“…To overcome this shortcoming, NLP efforts have been developed and applied to collect and curate synthesis data in relevant literature, such as synthesis conditions and resulting phases 25,98,99,160 . However, because of inherent biases in published results, the lack of negative examples (i.e., failed synthesis attempts) limits the ability to learn which factors contribute to an experiment's success 100,161 . Interestingly, the potential of coupling NLP with autonomous synthesis platforms has been demonstrated by the work of Mehr et al, where a fully integrated system was built to carry out the synthesis of organic compounds with experimental parameters parsed directly from the literature 162 .…”
Section: Decision Makingmentioning
confidence: 99%
“…ML has now started to be gradually and thoroughly applied to materials science and has already brought many promising applications to SSE research. In the case of LIB SSE prediction, we can see that ML algorithms perform well: helping researchers extend datasets by text mining from the literatures [ 36 , 80 ], providing new tools for screening SSE with high mechanical properties or high ionic conductivity. In terms of predicting materials, the reduction of computational cycles is undoubted great importance.…”
Section: Views and Conclusionmentioning
confidence: 99%
“…Another emerging application of ML that is tangentially related to SSB research is the text-mining of scientific publications (Kononova et al, 2021). Olivetti and coworkers demonstrated that text-mining can be used for extracting synthesis prescriptions from the literature and that this approach can be applied to the prediction of synthesis conditions for solid electrolytes (Mahbub et al, 2020;Olivetti et al, 2020).…”
Section: Figure | (A)mentioning
confidence: 99%